Characteristics and job satisfaction of general practitioners using Complementary and Alternative Medicine (CAM) in Germany - is there a pattern? - Joos, Stefanie; Musselmann, Berthold; Szecsenyi, Joachim; Götz, Katja (BMC complementary and alternative medicine, 2011)
Background: The use of Complementary and Alternative medicine (CAM) has increased over the past years. In Germany, many general practitioners (GPs) use CAM in their daily practice. However, little is known about possible differences of GPs using CAM compared to GPs not using CAM. The aim of the study was to explore differences in personal and practice characteristics, work load and job satisfaction of GPs depending on their use of and attitude towards CAM. Furthermore, predictors for CAM use should be explored. Methods: A questionnaire was developed based on qualitatively derived data. In addition, a validated instrument assessing job satisfaction was included in the questionnaire, which was sent to 3000 randomly selected GPs in Germany. Results: 1027 returned the questionnaire of which 737 indicated to use CAM in daily practice. We found that GPs using CAM are more female, younger and have a trend towards a healthier life style. Their practices have higher proportions of privately insured patients and are slightly better technically equipped with ultrasound. GPs with a positive attitude had significant better values within the job satisfaction scale and lower working hours per week compared to GPs with neutral/negative attitude. Significant predictors for CAM use were a positive attitude towards CAM, holding a special qualification in CAM, own CAM use and the availability of an ultrasound in practice. Conclusions: The identified differences suggest that those GPs using and believing in CAM have a different medical orientation and approach which in turn may influence their job satisfaction. With this finding CAM use turns out to be a relevant factor regarding job satisfaction and, with this, may be a possible lever to counteract the growing dissatisfaction of GPs in Germany. This finding could also be important for designing strategies to promote the recruitment of young doctors to general practice.